1993
DOI: 10.1111/j.1432-1033.1993.tb17707.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and kinetic mechanism of the inositol monophosphatase reaction and its inhibition by Li+

Abstract: Lithium-sensitive inositol monophosphatase from bovine brain was purified from brain and from a recombinant strain of Escherichia coli BL21-DE3. The natural and recombinant enzymes displayed identical physical and kinetic properties. At low [Li'], Li' inhibited the hydrolysis of racemic myo-inositol 1 -phosphate, myo-inositol4-phosphate and adenosine 2'-phosphate in a linear uncompetitive manner with apparent K, values of 1.1, 0.11 and 1.52mM, respectively. At Li' concentrations higher than 4 mM, Li' acted as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
111
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(124 citation statements)
references
References 34 publications
13
111
0
Order By: Relevance
“…The N-terminal signal peptide, which in vivo targets MtHPP to chloroplast, was determined by the TargetP version 1.1 server (45,46). The cleavage was predicted to occur between Arg 51 and Ala 52 , and the overexpressed construct was designed to yield the final protein with sequence starting from Met 53 . Enzymatic tests revealed that indeed, in the presence of Mg 2ϩ , MtHPP was able to hydrolyze HOLP to HOL, with the release of inorganic phosphate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-terminal signal peptide, which in vivo targets MtHPP to chloroplast, was determined by the TargetP version 1.1 server (45,46). The cleavage was predicted to occur between Arg 51 and Ala 52 , and the overexpressed construct was designed to yield the final protein with sequence starting from Met 53 . Enzymatic tests revealed that indeed, in the presence of Mg 2ϩ , MtHPP was able to hydrolyze HOLP to HOL, with the release of inorganic phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore very likely that only Mg 2ϩ binding site 1 with K d Ϸ 300 M (68) and site 2 with K d Ϸ 3 mM (69) are occupied in vivo. More importantly, Mg 2ϩ bound at site 1 was reported to remain tethered throughout the entire catalytic cycle, unlike Mg 2ϩ at site 2 that binds and dissociates over the course of the reaction (53,61,62).…”
Section: Mthpp and Impases; Comparison Of The Reaction Mechanism-mentioning
confidence: 99%
“…Chhetri et al (2005Chhetri et al ( , 2006 have already established the occurrence of the prime enzyme of myo-inositol biosynthesis, MIPS, in pteridophytes. Therefore, the presence of MIPP adds (Eisenberg Jr. 1967, Attwood et al, 1988Gee et al, 1988;Honchar et al, 1989;Leech et al, 1993;Pollack et al, 1994;Caselli et al, 1996, Fujimoto et al, 1996, Nigou and Besra, 2002Wang et al, 2006;Patra et al, 2007). However, its kinetic parameter, thermo-tolerance and calciumdependent inhibition at lower concentrations, differ substantially in pteridophytic species.…”
Section: Discussionmentioning
confidence: 99%
“…In pteridophytes, Benaroya et al (2004) and Chettri et al (2005Chettri et al ( , 2006 have recently documented the occurrence and characterization of L-myo-inositol-1-phosphate synthase. So far, work with regard to the participation of the subsequent enzyme in this metabolic sequence, myo-inositol-1-phosphate phosphatase (MIPP), has been carried out principally in animal systems (Eisenberg Jr, 1967;Attwood et al, 1988;Gee et al, 1988;Honchar et al, 1989;Leech et al, 1993;Pollack et al, 1994;Kwok and Lo, 1994;Fujimoto et al, 1996;Caselli et al, 1996), in archaea (Wang et al, 2006), in bacteria (Nigou and Besra, 2002), and in cyanobacteria (Patra et al, 2007). However, only a few reports are available of this enzyme from plant systems (Loewus and Loewus, 1983;Gumber et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The phosphatase reaction of Li ϩ -sensitive phosphatases has an absolute requirement for metal ions and has been suggested to proceed through the activation of a water molecule and its subsequent nucleophilic attack on the removable phosphorus atom (57,58). It is still not clear how many metal ions are required for the activation of the nucleophilic water molecule, and two catalytic models have been proposed.…”
Section: E Coli Has Two Genes Encoding the Type II (Glpx-like)mentioning
confidence: 99%